Rancang Bangun Alat Bantu Panjat Pohon Kelapa - Baso Nasrullah; Syaharuddin Rasyid; Muh. Rachmat Fajrin; Arwandis Arwandis (Politeknik Negeri Ujung Pandang, 2021)
The design of coconut tree climbing aids purposes to make it easier and provide a sense of security to climb trees even though they do not have climbing skills. This tool uses a 2024 series hollow aluminum material which has a maximum tensile strength of 302 MPa which is able to withstand a force of 7097Nmm which is greater than the maximum force that occurs which is 2000Nmm. This material has the ability to withstand a moment of 450.282Nmm greater than the moment that occurs of 100,000 Nmm, so the operator is safe without worry breaking. The testing of this tool has been proven to make it easier for humans who do not have climbing skills to a height of 6 m while those who have skills to climb coconut trees without tools can only reach a height of 3 m. this is because climbers who have skills still feel awkward using coconut tree climbing aids. So it can be concluded that this climbing aid is safe and even people who do not have climbing skills can climb coconut trees safely.